The Analysis of Vasculopathy Risk Factors to the Incidence of N-AION - Intan Oktaviana; Riski Prihatningtias (Majalah Oftalmologi Indonesia, 2015)
Background: Nonarteritic Anterior Ischemic Optic Neuropathy (N-AION) is an optic disc oedem caused by ischemic process. The disease often occured at old age population and threatening the vision. Vasculopathy was assumed to accelerate the ischemic process in the incidence of N-AION. The purpose of this study is to analyze the vasculopathy risk factors that play a role to the incidence of N-AION in Kariadi Hospital Semarang. Methods: This was an analytic observational study with chi square test. Samples were obtained from patient’s medical record who were diagnosed as N-AION in Kariadi Hospital eye’s clinic from January 2012 to June 2014. The data included vasculopathy risk factors consisting of hypertension (blood pressure >140/80 mmHg), diabetic Mellitus (blood sugar >200mg/dl) and dislypidemia, including hypercholesterolemia (>200 mg/dl), hypertriglyceride (>150 mg/dl) and the increase of LDL level (>140 mg/dl). All the data was analysed by SPSS 15.0. Results: A total of 31 patients of N-AION were reviewed, 20 patients (64,5 %) had risk factors of hypertension and those with diabetic mellitus. Twenty five patients (80.6%) were hypercholesterolemia, 15 patients (48.4%) were hypertriglyceride and 11 patients (25.5%) had increasing LDL level. The statistical testing using chi square test (α = 0,05) resulted only hypercholesterolemia (p=0.001) which had a significant correlation with the incidence of N-AION, meanwhile hypertension (p=0.106), diabetic mellitus (p=0,106) and hypertriglyceride (p=0.857) had no significant correlation. Conclusion: Statistic analysis of vasculopathy risk factors to the incidence of N-AION indicates that hypercholesterolemia is the most influence risk factor. Keywords: N-AION, risk factor, vasculopathy